Intracellular cross-talk between receptors coupled to phospholipase C via pertussis toxin-sensitive and insensitive G-proteins in DDT1MF-2 cells. - Dickenson, J. M. (Nature Publishing Group, 1993)
1. The effect on intracellular free calcium concentration ([Ca2+]i) of simultaneous activation of receptors coupled to phospholipase C via pertussis toxin (PTX)-sensitive and -insensitive G-proteins has been investigated in the hamster vas deferens smooth muscle cell line, DDT1MF-2. 2. In fura-2-loaded DDT1MF-2 cells, activation of adenosine A1-receptors (which are linked to PTX-sensitive G-proteins) with a maximal concentration of N6-cyclopentyladenosine (CPA; 300 nM) increased [Ca2+]i from 121 +/- 5 nM to 254 +/- 20 nM (n = 8). These experiments were performed in the presence of extracellular Ca2+. Stimulation of histamine H1-receptors (which are linked to PTX-insensitive G-proteins) with a low concentration of histamine (1 microM) increased [Ca2+]i from 128 +/- 8 nM to 150 +/- 13 nM (n = 8). When combined, CPA (300 nM) and histamine (1 microM) synergistically raised [Ca2+]i from 134 +/- 6 nM to 607 +/- 61 nM (n = 8). 3. Removal of extracellular Ca2+ (experiments performed in Ca(2+)-free buffer containing 0.1 mM EGTA) had no effect on the synergistic interaction between CPA (300 nM) and histamine (1 microM). 4. The addition of maximal concentrations of CPA (300 nM) and histamine (100 microM) resulted in a rise in [Ca2+]i which was additive when compared to the Ca2+ responses obtained with the two agonists alone. Low (30 nM) and subthreshold (3 nM) concentrations of CPA did not alter the Ca2+ response elicited by maximal concentrations of histamine (100 microM). 5. Subthreshold concentrations of CPA (3 nM) and low concentrations of histamine (1 microM) elicited synergistic rises in [Ca2+]i.(ABSTRACT TRUNCATED AT 250 WORDS)